2018
DOI: 10.1038/s41598-018-25586-3
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effect of Date syrup on radiation- induced damage in Rats

Abstract: Ionizing radiation has cytotoxic and genotoxic effects caused mainly by the oxidative damage induced by free radical release. The need for radioprotectives is increasing to protect normal tissues during radiotherapy. In the present study, we investigated the radioprotective effect of Date syrup in rats subjected to whole body radiation at 6 Gy through biochemical, molecular and histopathological analysis. Significant elevations were recorded in the activities of serum ALT, AST, ALP and LDH and in the levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 72 publications
5
26
0
Order By: Relevance
“…The present investigation suggests that the hemoglobin level follows a same pattern to that of RBC in general. These observations are in agreement with Zeid et al, 18 who reported significant reduction in hemoglobin concentration in Swiss albino mice exposed to 6 Gy gamma radiation. A depression in the hematocrit value can be related to total cell depletion in peripheral blood aided by confusion in steady state mechanisms in blood forming organs as well as an increase in plasma volume after irradiation.…”
Section: Fig 2: Showing Correlation Coefficient Among Various Group supporting
confidence: 93%
“…The present investigation suggests that the hemoglobin level follows a same pattern to that of RBC in general. These observations are in agreement with Zeid et al, 18 who reported significant reduction in hemoglobin concentration in Swiss albino mice exposed to 6 Gy gamma radiation. A depression in the hematocrit value can be related to total cell depletion in peripheral blood aided by confusion in steady state mechanisms in blood forming organs as well as an increase in plasma volume after irradiation.…”
Section: Fig 2: Showing Correlation Coefficient Among Various Group supporting
confidence: 93%
“…911 ROS cause cellular damage by causing adverse effects on antioxidant defense mechanisms by reducing glutathione (GSH) levels and increasing malondialdehyde (MDA) levels. 12,13 Recent studies have also shown that ROS cause damage to DNA and lead to caspase-dependent apoptosis. 14,15 Activation of the caspase-3 cascade plays a highly important role in apoptosis and is regarded as a terminal event prior to cell death and increases under the effect of radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation induced (OS) results in oxidation of protein, lipids and nucleotides (Sarhanand & Naoum, 2020). Therefore ionizing radiation is known to induce mutations and cell transformations through single and double strand DNA breakage leading to produce chromosomal instability and carcinogenesis (Vorobtsova, 2000;Bàlentovà et al, 2008;Abou-Zeid et al, 2018). Clear dose rate effects were observed in MNPCEs and CAs frequencies in mice and rats (Tanaka et al .,2008;Pillai & Devi, 2013;Bagheri et al,2018).…”
Section: Introductionmentioning
confidence: 99%